Estratégia de minimização de perdas para um gerador de indução duplamente alimentado - Soares, Marcelo Nesci (2017)
This work presents a theoretical study of a control strategy that seeks to mitigate the inherent electrical losses due to copper and iron of a doubly fed induction machine. This strategy consists in finding the optimum reactive power sharing between the rotor and stator circuits of the generator. As this work is motivated to reduce costs and improve system efficiency, this research is focused on variable speed generation systems using a doubly fed induction machine. In this topology, the cost of power electronics converter is reduced drastically since the sizing is related to slip power of the generator. In this work a modeling of a doubly fed induction machine considering iron losses is proposed besides the strategy of vector control responsible for controlling the active and reactive power flow in the generator by the converters. The adaptation by module is the technical optimum design method used to set the controllers parameters. As loss-minimisation strategy requires a significant effort from converters, a model for computing semiconductor losses, IGBT type, is showed and compared with other software to validate the model. The simulation results confirm the existence of a minimal point of losses in the generator when the reactive power sharing is applied. In addition, the results show that the use of this strategy does not compromise the power factor at the point of common coupling neither increase the converter losses.